Baseline Parameters for Rotational Thromboelastometry in Healthy Laboring Women: A Prospective Observational Study. Issue 1 (24th March 2021) - Lee, J.; Eley, V.A.; Wyssusek, K.H.; Kimble, R.M.N.; Way, M.; Coonan, E.; Cohen, J.; Rowell, J.; van Zunderta, A.A.
Abstract : ( BJOG . 2020;127:820–827) The point-of-care test used for determining whole blood coagulation data, known as rotational thromboelastometry (ROTEM), is used in hepatic and cardiac surgery, obstetrics, and trauma. Normal ROTEM ranges for clotting time and maximum clot firmness in pregnant, term women in labor have not been previously studied. The primary aim of this study was to establish baseline ROTEM parameters for healthy term laboring women. Furthermore, a secondary aim was to compare these results to previous studies' reference ranges and the manufacturer's ranges for the nonobstetric population.